PENGARUH CONFIRMATION BIAS DAN RISKY CHOICE FRAMING TERHADAP KEPUTUSAN INVESTASI PETANI - Ryan Elfahmi; Endang Puji Astutik; Kemas Vivi Andayani (Sekolah Menengah Kejuruan (SMK) Pustek, 2022)
This study aims to determine the effect of Confirmation Bias and Risky Choice Framing on farmers' investment decisions. The questions in this study are whether Confirmation Bias affects farmers' investment decisions and whether Risky Choice Framing affects farmers' investment decisions. The analysis technique in this research includes correlation test, determination test and F test which is a model feasibility test, followed by multiple linear regression analysis and hypothesis testing (t). The sample method uses purposive sampling, with several criteria developed previously. Questionnaires were used to collect data from respondents. Respondents in this study were farmers in Blubur Limbangan District, Garut Regency. In total there are 356 respondents. Based on the results of hypothesis testing (t), Confirmation Bias affects farmers' investment decisions and Risky Choice Framing affects farmers' investment decisions.